Leadership and employee attitudes: The mediating role of perception of organizational politics - Uzair Khuwaja; Kaleem Ahmed; Ghulam Abid; Ahmad Adeel (Cogent Business & Management, 2020)
Leadership practices/styles remain a key focus for organizational researchers from decades. Researcher's believe that a leaders realization of his potentials following particular style bring influential consequences in performances. The present study aimed to add support to researcher's believe that certain leadership style (paternalistic and servant) will not only positively influence employee's attitude (job satisfaction and commitment), but also help to minimize negative perceptions (perceptions of organizational politics). Using a sample data of 320 employees working in largest public sector Electricity Distribution Company of Pakistan in 6 different districts and 115 offices, the study investigate the relationships between studied variables. Data was analyzed via structural equational modeling, providing evidence that both paternalistic and servant leadership styles has positive influence on employees job satisfaction commitment levels and negative political perceptions. The results also showed that relationship between paternalistic leadership style and employee attitude is mediated by perception of politics but not for servant leadership style. Our results contribute to literature by providing empirical evidences and identifying which particular leadership style benefits in public sector organizations in Asian countries. More investigations based on different contexts and employee attitudes are discussed and suggested in future research and implications.
Keywords: 650; Paternalistic leadership; servant leadership; perception of organizational politics; commitment; satisfaction; public sector